FRUIT YIELD AND NUTRITIONAL CHARACTERISTICS OF SWEET PEPPER GROWN UNDER SALT STRESS IN HYDROPONIC SYSTEM1 - NADIELAN DA SILVA LIMA (Revista Caatinga, 2018)
Irrigation with brackish water is common in the semiarid region of the Brazilian Northeast, potentiating the process of salinization of the soil in these areas. The hydroponic system stands out as an important strategy for crop management in semiarid regions, since crops show greater tolerance to the salt stress under hydroponic conditions, which minimize the effects of soil salinization. Thus, the objective of this work was to evaluate the effects of salt stress on the growth, fruit yield and mineral nutrition of sweet pepper in hydroponic system, using brackish water and coconut fiber substrate. The experiment was conducted in Recife, State of Pernambuco, Brazil (8°3'15''S, 34°52'53''W). A randomized block experimental design in a 5x2 factorial arrangement with five replications was used, consisting of five water salinity levels of the nutrient solution (2.0; 3.5; 4.5; 5.5 and 6.5 dS m-1) and two sweet pepper cultivars (Bruno and Rubia). The increasing salinity level of the nutrient solution decreased the fruit yield of the cultivars evaluated, reduced the potassium, phosphorus and sulfur, and increased the sodium and chlorine contents in the leaf tissues. The Ca contents of the cultivar Bruno decreased with increasing salinity, and increased in the cultivar Rubia. The cultivar Rubia stood out with the highest fruit yield and ionic selectivity, accumulating high amounts of potassium and calcium and maintaining low Na and Cl contents. The fruit yield of the cultivar Rubia (39.9 t ha-1) grown under solution with electrical conductivity of up to 3.5 dS m-1, denotes the potential viability of growing this cultivar under hydroponic conditions.